2013
DOI: 10.1371/journal.pone.0066230
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of DNA Methylation during Early Development of the Preimplantation Bovine Embryo

Abstract: There is species divergence in control of DNA methylation during preimplantation development. The exact pattern of methylation in the bovine embryo has not been established nor has its regulation by gender or maternal signals that regulate development such as colony stimulating factor 2 (CSF2). Using immunofluorescent labeling with anti-5-methylcytosine and embryos produced with X-chromosome sorted sperm, it was demonstrated that methylation decreased from the 2-cell stage to the 6–8 cell stage and then increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 48 publications
6
87
2
2
Order By: Relevance
“…This suggests that the male embryo is more susceptible to early gestational intervention than the female, as seen in the in vitro embryo (Bermejo-Alvarez et al 2011), and that this effect continues until at least 98dpc. The reason for this gender difference may be that the pattern of DNA methylation during embryo development in the two sexes is different over time making susceptibility to epigenetic change both gender and time dependent (Dobbs et al 2013). We note however, that the expected gender effect on birthweight where the male is larger and heavier than the female was not observed in this study.…”
Section: Sexual Dimorphismcontrasting
confidence: 74%
See 1 more Smart Citation
“…This suggests that the male embryo is more susceptible to early gestational intervention than the female, as seen in the in vitro embryo (Bermejo-Alvarez et al 2011), and that this effect continues until at least 98dpc. The reason for this gender difference may be that the pattern of DNA methylation during embryo development in the two sexes is different over time making susceptibility to epigenetic change both gender and time dependent (Dobbs et al 2013). We note however, that the expected gender effect on birthweight where the male is larger and heavier than the female was not observed in this study.…”
Section: Sexual Dimorphismcontrasting
confidence: 74%
“…The gender of an embryo has also been shown to affect the susceptibility of the embryo to altered nutrition before mating (Vinsky et al 2006). Gender-specific differences in embryo DNA methylation pattern (Dobbs et al 2013), expression of key developmental genes (Kwong et al 2006), fetal and placental perfusion (Prior et al 2013) post-natal carcass traits (Micke et al 2011) have all been reported. Intriguingly, neonatal and fetal death in cattle is increased if the fetus is male, as with most mammalian species.…”
Section: Introductionmentioning
confidence: 99%
“…ImageJ software was used to quantify concentrations of H3K4me2, H3K9me2, and DNA staining. Results are presented as a percentage of the average fluorescence intensity of each specific antibody (H3K9me2 and H3K4me2) divided by the fluorescence intensity of DNA as previously described [47].…”
Section: Immunofluorescence Of Blastocyst Stage Embryosmentioning
confidence: 99%
“…These conflicting results were not only found between these two analytical methods, but also between studies using the same staining method. There is disagreement in whether methylation is higher in ICM or TE of blastocysts (Dean et al 2001;Hou et al 2007;Dobbs et al 2013;Li et al 2014), and differences in staining protocols may be responsible for the conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…A common method used to study DNA methylation of preimplantation embryos is 5-methylcytosine (5-mC) immunofluorescence staining (Dean et al 2001;Hou et al 2007;Dobbs et al 2013). However, conflicting results were found among these studies, for example as to whether methylation is more intensive in inner cell mass (ICM) or trophectoderm (TE) cells in IVF bovine blastocysts, and the staining result can be affected by the protocol used (Li and O'Neill 2012).…”
mentioning
confidence: 99%